EFEKTIVITAS PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA KIMIA PADA MATERI IKATAN KIMIA TERHADAP HASIL BELAJAR SISWA KELAS X SMA/MA - Maulidina, Yuliani (journal of residu, 2019)
This research is motivated by the availability of a snake ladder chemical game media on chemical bonding material that has not been tested for effectiveness on student learning outcomes. This study aims to reveal the effectiveness of the use of snake ladder chemical media on chemical bonding material on the learning outcomes of class X SMA / MA students. This type of research is quantitative descriptive. The design of this study is Pre-experiment, One Group Pretest-Posstest Design. The population in this study were students of class X IPA SMAN 1 2x11 Kayu Tanam. The research sample was taken by using probability sampling techniques so that the class X MIPA 3 was selected as the sample class. The data analysis technique used is the N-Gain test and the Normality test. The results showed that the lowest gain value was 0.4 (medium), while the highest gain was 1.00 (high). Average Gain is 0.76 (high). In the data processing technique with SPSS 16 for the sample test it was found that the sample was not normally distributed and Wilcoxon showed that the significance value produced was 0,000 <0,05 from the significance level showing the media playing chemical snakes and ladders improving learning outcomes. So it can be concluded that the use of media snakes and ladders games is effectively used in chemistry subjects especially in chemical bonding material.